2013
DOI: 10.1109/tcpmt.2012.2236384
|View full text |Cite
|
Sign up to set email alerts
|

Use of Harsh Wafer Probing to Evaluate Traditional and CUP Bond Pad Structures

Abstract: IC pad damage from a wafer probe can be detrimental to wire-bond yield and product reliability. In this paper, bond pads are harshly probed on traditional pads and a variety of experimental circuit-under-pad (CUP) structures in technologies having aluminum (Al) metallization and silicon dioxide (SiO 2 ) dielectric films. Probe marks and cracking behavior are analyzed, seeking process margins for high-reliability products. Results follow the well-known dependencies on chuck overdrive, probe touch counts, and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…This probe cracking trend closely matches trends reported from our previous harsh probing experiments [1]. High MT(-1) pattern density pads are the weakest, showing the most ripple and cracking when harshly probed.…”
Section: Figure 12 Fraction Of Pads Cracked In Probing Vs Pattern Den...supporting
confidence: 89%
See 1 more Smart Citation
“…This probe cracking trend closely matches trends reported from our previous harsh probing experiments [1]. High MT(-1) pattern density pads are the weakest, showing the most ripple and cracking when harshly probed.…”
Section: Figure 12 Fraction Of Pads Cracked In Probing Vs Pattern Den...supporting
confidence: 89%
“…Cracks initiate due to stress from probing, bonding, or both. Our previous work has shown much about the mechanisms of cracking, characteristics of cracks from harsh probing and wirebonding, and how to design pad structures to prevent cracks [1][2][3][4]. Cracking tendency of pad structures is witnessed by observing the "ripple effect" in the destructive "cratering test", where wirebonds and pad Al are removed to permit inspection by optical microscope.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies explored the failure mechanism of ILD crack in copper wire bonding. Through mechanical simulation and modeling, different wafer structures can impact ILD crack (Wang et al, 2007;Hunter et al, 2011). In the study of C40 wafer on BGA package, proper wire bonding parameters were required to avoid the ILD crack (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid damaging the pads on the IC device during the wafer test procedure, it is necessary to limit the contact force and scrub mark length in accordance with the material and dimensions of the pad. Hunter et al [9] used a cantilever probe to conduct the probing test. The experiment observations confirmed that overdrive dominates in causing cracks, while 2156-3950 © 2014 IEEE.…”
Section: Introductionmentioning
confidence: 99%